Structural Study of SrTiO3 Single Crystal using High Resolution X-ray Diffraction - Abdullah, Aziz Muhemed (Sulaimani Journal for Pure and Applied Sciences, 2013)
Strontium titanate, SrTiO3 is one of the perovskite – type crystal that commonly used as a substrate for epitaxial growth of multifunctional oxide films and well-defined TiO2-terminated surface is crucial for the fabrication of oxide hetero-interfaces. Structural properties have a strong effect on thin films characteristics and their applications. Proceeding from this fact, the lattice defects of as-grown or as-annealed SrTiO3 single crystals with a nondestructive technique have been investigated. The structural imperfection and dislocation density (screw and edge types) of STO single crystals with 10x10x1 mm dimension (from crysTec GmbH- Berlin) have been studied using omega scan from high-resolution x-ray diffraction technique, as well as, the symmetric (002) and the skew-symmetric (101) rocking curves (which are sensitive to the structural perfection) also reported. In order to prove the sample quality, the experimental full widths at half maximum (FWHM) of the X-ray rocking curves have been shown. From the FWHMs, the dislocation density (screw and edge types) and the total dislocation density have been calculated.
Keywords: High resolution xray diffraction; Rocking curve; FWHM; Dislocation density